The Application of Task-Based Learning to Improve the Quality of The Teaching and Learning Process of Reading in Indonesian Secondary Schools Context - Wulandari, Maria; Syafrianto, Syafrianto (Jurnal Inovasi Pendidikan MH Thamrin, 2018)
This paper aims to discover the feasibility and the applicability of task-based learning in improving the quality of the teaching and learning process (TLP) of reading in Indonesian secondary schools in relation to the teaching of genre or text types as required by the national curriculum. This is an action research study which is qualitative in nature. The data were obtained through observations and interviews with the students and the collaborators. They were in the forms of field notes, interview transcripts, and photographs. In addition, this research applied the investigator triangulation, the theoretical triangulation and the time triangulation.Â The actions implemented in this research are discussing new vocabulary items and guessing meaning from context, applying skimming and scanning strategies, discussing grammar related to the text, conducting a question/answer game, providing various materials from different sources, and applying group/pair work. The results of the research show that the studentsâ€™ motivation increased. They were more enthusiastic in learning reading. Moreover, the students were interested in various materials presented by the teacher. They could get involved actively in the reading learning process. In addition, the classroom interaction also increased. The students could interact very well with other students and the teacher. In conclusion, the use of task-based approach with its accompanying actions is effective to improve the teaching and learning process of reading.